UMP prihatin santuni anak-anak istimewa - Nor Salwana, Mohammad Idris (2020)
Kuantan, 18 August 2020 - Researchers from the Faculty of Civil Engineering Technology (FTKA), Universiti Malaysia Pahang (UMP) successfully developed a high-level disinfectant (HDL), Diaclean Pera Sterilant which contains the active ingredient peracetic acid from food vinegar that can kill 99.99% of microorganisms such as bacteria, viruses, fungi and protozoa.